A Novel H1N2 Influenza Virus Related to the Classical and Human Influenza Viruses from Pigs in Southern China - Song, Yafen; Wu, Xiaowei; Wang, Nianchen; Ouyang, Guowen; Qu, Nannan; Cui, Jin; Qi, Yan; Liao, Ming; Jiao, Peirong (Frontiers in Microbiology, 2016)
Southern China has long been considered to be an epicenter of pandemic influenza viruses. The special environment, breeding mode, and lifestyle in southern China provides more chances for wild aquatic birds, domestic poultry, pigs and humans to be in contact. This creates the opportunity for interspecies transmission and generation of new influenza viruses. In this study, we reported a novel reassortant H1N2 influenza virus from pigs in southern China. According to the phylogenetic trees and homology of the nucleotide sequence, the virus was conﬁrmed to be a novel triple-reassortant H1N2 virus containing genes from classical swine (PB2, PB1, HA, NP, and NS genes), triple-reassortant swine (PA and M genes) and recent human (NA gene) lineages. It indicated that the novel reassortment virus among human and swine influenza viruses occurred in pigs in southern China. The isolation of the novel reassortant H1N2 influenza viruses provides further evidence that pigs are ‘‘mixing vessels”, and swine influenza virus surveillance in southern China will provide important information about genetic evaluation and antigenic variation of swine influenza virus to formulate the prevention and control measures for the viruses.